Evaluation of Pharmacy Model in a Trial of Free Essential Medicine Access - Muhamad Z. Ally; Nav Persaud; Norman Umali (SAGE Publishing, 2020)
Background: In Canada, pharmacists accessing electronic health records (EHR) and mailing medications to patients are relatively uncommon. We evaluated a pharmacy model implemented in a clinical trial that combined allowing the pharmacist access to patients' EHR and mailing medications to participants. Methods: We conducted thematic analysis of comments made by participants and prescribers, and chart stimulated recalls with the pharmacist involved with the novel pharmacy model implemented in a clinical trial. Results: Major themes from participant's comments related to the ease of obtaining information about medications from the pharmacy and satisfaction with the delivery. Prescribers felt that this model facilitated collaboration with the pharmacist and welcomed suggestions regarding therapeutic medication changes. Major themes from the pharmacist's chart stimulated recalls were that access to participants' EHRs allowed for improved drug therapy management and participant experience, and this pharmacy model increased participant's access to pharmacy services. Discussion: According to the pharmacist and prescribers, this pharmacy model facilitated their collaboration in prescribing appropriate medications and participants were generally satisfied with the delivery of medications. Conclusion: Participants and prescribers were generally supportive of a pharmacy model that combined allowing the pharmacist access to participants' EHR and medication mailing. This allowed the pharmacist more opportunities for drug therapy management and collaboration with prescribers. It also improved the participant's access to pharmacy services, although those services were not always fully utilized.